Using Google Classroom in Teaching Recount Text at the Tenth Grade Students of Vocational School (SMK) - Johan, Andrian Nuriza; Apriliandita, Denita Teza Ayu; Widodo, Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aimed to obtain the empirical evidence whether or not Google Classroom has good effect in improving students’ writing Recount Text. This research belongs to quantitative research using quasi experimental design. The population of this research was the tenth grade students of SMK Batik Perbaik in the academic year 2021/2022. The samples of this research were OTKP 1 as a experimental group and OTKP 2 as a control group, The experimental group was treated by using Google Classroom and the control group was treated without Google Classroom. The writer took a pre-test that the classes have relatively the same background knowledge in the research variable and a post-test was to find out the growth of score as measurement of achievement. this research showed that the students progress experimental group in recount text was good. It could be seen score of experimental group was 78.96 and the mean score of control group was 61.28. the highest score of experimental group was 88 and the highest score of control group was 80. The both scores were categorized good. To see whether the hypothesis was accepted or rejected, the researcher used t-test. The result of t-test was higher than t-table that 4.104>2009, so there was a significant difference in students’ achievement between those who were taught recount text using google classroom and the students who were taught recount text without using google classroom Keywords: English writing, Recount text, Google Classroom